The Relationship between Dimensions of Collective Action, Introversion/Extroversion, and Collective Action Endorsement among Women. Issue 1 (1st June 2021) - Tassone, Adrianna; Foster, Mindi D.
Abstract: Given the psychosocial benefits of collective action for minority group members, we explored how the personality trait introversion/extroversion may contribute to current understandings of what motivates collective action among women. Dimensions of collective action that are consistent with introversion (e.g., low risk) were expected to predict greater endorsement of collective action among introverts, whereas dimensions consistent with extroversion (e.g., public) were expected to predict greater endorsement among extroverts. One hundred and seventy-nine women completed an online questionnaire, and regression analyses showed that among introverts, collective action rated lower in risk and social cost, but higher in effectiveness and formality predicted greater endorsement. Among extroverts, collective action rated as more public (vs. private) predicted greater endorsement. The implications of utilizing personality profiles to enhance collective action are discussed.